SYNTHESIS STUDY OF SN- BASED PEROVSKITE CS2SNI6 AND ITS APPLICATION ON HHYBRID BULK- HETEROJUNCTION SOLAR CELL - Khaeroni, Rany
The research of perovskite materials is currently very rapid to investigate from the study of methods, synthesis, and its application for electronic and optoelectronic devices. In general, perovskite materials have an ABX3 structure that has an interesting physical property, i.e. the band that corresponds to the electrode layer or the active polymer of solar cells, so that it can be utilized as an electron transport layer (ETL). In several years, the use of Pb-based perovskite in solar cells has reached efficiency of more than 20%, but the constraints of toxicity and safety to the environment from Pb hinder the development of these type solar cells. In order to overcome this problem, there are some study of the Sn-based perovskite, Cs2SnI6 which is environmental friendly and easy synthesized, can be synthesized free air and at room temperature. Recently, the application of perovskite material is mostly come as light absorption or as an electron transport layer in solar cell devices both for the generation of dye sensitized solar cells and bulk- heterojunction solar cells. In this study, we attempt to synthesis Sn-based perovskite (Cs2SnI6) and to fabricate the inverted - heterojunction of solar cell with or without incorporation of perovskite Cs2SnI6 as light absorption in the active layer of P3HT:PCBM and as electron transport layer in order to improve the performance and the life time the devices. The synthesis of Cs2SnI6 perovskite was carried out by chemical methods from the main material that are Cs2CO3, SnI4, HI, and ethanol solvent. All the material are mixed in air and room temperature. In order to optimize the solubility of Cs2SnI6 in organic solvents, a synthesis control of this type of perovsite was carried out in several solvents and the best volume ratio was obtained for the solubility of perovskite is 1:10 in GBL and acetonitrile. The XRD characteristic of the Cs2SnI6 perovskite produce a Fm3m space group (225) with lattice parameter of 11.66276 Å, and an optical band gap of 3.1 eV The fabrication of BHJ hybrid solar cells was carried out by spin coating method in configuration of ITO / ZnO / P3HT: PCBM / PEDOT: PSS / Ag. Perovskite Cs2SnI6 as electron transport layer was deposited between ZnO layers and v P3HT:PCBM, while perovskite Cs2SnI6 as absorber was added into solution of P3HT:PCBM with a concentration of 0.31wt% and then deposited with a spin coating method above ZnO layer. The J-V characterizations of inverted bulk- heterojunction show that the effect of Cs2SnI6 perovskite material as absorber in the polymer active layer results in current density (Jsc), open voltage (Voc), and power conversion efficiency of 49.70 mA/cm2, 0,46 V, and 6.15% respectively, while the device without perovskite was 64.69 mA/cm2, 0.41 V, and 7.05% respectively. In the incorporation of Cs2SnI6 perovskite as ETL, the perovskite layer produces current density (Jsc) and open voltage (Voc) values of 77.02 mA/cm2 and 0.47 V respectively and it can increase the efficiency of power conversion from 7.05% to 9.75% when the Cs2SnI6 perovskite layer is used with a concentration of 2.25 mg/ml. Finaly, the best method for adding a Cs2SnI6 perovskite layer in a bulk- heterojunction solar cell is by used of spin coating method.